Future of food: journal on food, agriculture and society (The Department of Organic Food Quality and Food Culture at the University of Kassel, Germany : Federation of German Scientists (VDW), 2013)
"The Department of Organic Food Quality and Food Culture at the University of Kassel, Germany and the Federation of German Scientists (VDW) present a peer reviewed journal for young scholars and researchers. The aims of the journal are to create a platform for young scholars, researchers, post graduate students, doctoral students and post doctoral fellows who are interested in food related themes to deliberate their research experiences through research paper articles. As a multi-disciplinary journal, natural scientists and social scientists from all around the world are welcome to engage in this forum as contributors."--Journal homepage